VIOLÊNCIA DOMÉSTICA CONTRA CRIANÇAS E ADOLESCENTES: PREVALÊNCIA EM CIDADE DO SUL DO BRASIL - Lucimara Cheles da Silva Franzin; Fernanda Mara Franzin; Simone Tetu Moysés (Colloquium Vitae, 2012)
The aim of this study was to investigate domestic violence against children and adolescents in Curitiba-Pr. It was realized a descriptive exploratory research, with quantitative approach. It was analyzed the notification register basis of the Protection Network of children and adolescents at risk of violence in Curitiba-Brazil, 2004-2009. The variables included the socio-demographic profile of the victims, types of violence, origin of notification, information about the aggressor, severity of the case, injuries. The data had been stored in the software EPI-INFO and analyzed by software SPSS 17.0. It was analyzed the frequency distribution and associations between variables, using chi-square test, with the level of significance of 5%. The 19.316 notifications showed a prevalence of 88.4 of domestic violence, with 17,082 cases, as neglect with 9,742 notifications (57.0%). From the total, 43.9% of the cases were considered serious, the most affected age was 5 to 14 years old, with balance between genders. Among aggressors, the mother was the most important in cases of negligence. The physical sequels (20.2%) mainly reached head, arms and legs, characterized as bruising, cuts, and fractures. It was concluded that, in the studied period, domestic violence had greater visibility in this city, with more notifications of neglect. It is important to increase politics on domestic violence prevention, with continuous violence and family support strategies, supporting victims, family and aggressors.